BioEssays 7∕2019. (27th June 2019) - Page, Charlotte E.; Leggat, William; Heron, Scott F.; Choukroun, Severine M.; Lloyd, Jon; Ainsworth, Tracy D.
Abstract : Driving patterns of coral bleaching over reefs are a suite of biophysical interactions where the physical environment modulates organism response through an interplay with intrinsic biological functioning. Flow conditions over reefs can mitigate the physiological impacts of thermal stress across multiple spatial scales. More details can be found in article number 1800226 by Charlotte E. Page et al., Seeking Resistance in Coral Reef Ecosystems: The Interplay of Biophysical Factors and Bleaching Resistance under a Changing Climate, DOI: 10.1002/bies.201800226 .